Biofabrication of Scaffold-Free 3d Cellular Structures Using Magnetic Levitational Assembly To Study Cardiac Toxicity - Arslan Yıldız, Ahu; Yıldız, Ahu Arslan; Arslan Yıldız, Ahu; Onbaş, Rabia (Mary Ann Liebert, 2023)
Spheroids are one of the well-characterized 3D cell culture approaches for drug screening and therapeutic studies. Magnetic levitation (MagLev) is a newly developing approach to form 3D cellular structures and spheroids [1,2,3]. Magnetic levitational assembly of cells provides rapid, simple, cost-effective 3D cell culture formation while ensuring scaffold-free microenvironment. Here, our efforts are summarized in designing new magnetic levitation platform and biofabrication of 3D cellular entities via magnetic levitation for tissue engineering. Magnetic levitation and guidance of cells were provided by using a paramagnetic agent to fabricate scaffold-free 3D cellular structures. The parameters of cell density, paramagnetic agent concentration, and culturing time were optimized to obtain 3D cardiac cellular structures with tunable size, circularity, and high cell viability. Cellular and extracellular components of the 3D cellular structures were demonstrated via immunofluorescent staining. Also, 3D cardiac cellular structures showed more resistance to drug exposure compared to 2D control. In conclusion, MagLev methodology offers an easy and efficient way to fabricate 3D cellular structures for drug screening studies.
Tissue Engineering and Regenerative Medicine International Society (TERMIS) -- JUN 28-JUL 01, 2022 -- Krakow, POLAND
Keywords: Magnetic levitation; Scaffold-free tissue engineering; 3D cell culture; Drug screening assays